RANCANG BANGUN DAN UJI KINERJA MESIN PERAJANG TEMBAKAU MESIN PERAJANG TEMBAKAU SEMI MEKANIS SISTEM KAYUH - Sandra Sandra; Yoga Aditya Pratama; Gunomo Djoyowasito; Ary Mustofa Ahmad (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
Tobacco is a very promising export commodity for Indonesia. With a high selling price, tobacco can improve the economic level of the tobacco farming community. Problems that are often faced in the tobacco processing process are long and less efficient crafting processes. Therefore we need a tool to support an effective and efficient crafting process. The making of tools is done in Malang creative art welding workshop and tool testing is carried out in the power laboratory and agricultural machinery. The purpose of making this tool is to make the semi-mechanical tobacco chopper system paddle and test the performance of the chopper machine. The working principle of this machine is that the blade shaft that is connected to the pedaling pedal will rotate when the pedal is moved and will slice the leaves of tobacco that enter through the leaf input section. From the results of engine performance tests that have been made obtained the value of engine efficiency is 94% and the average capacity of 21.92 kg / hour and the power needed by the engine is 0.228 HP